Differentiation of human induced pluripotent stem cells into functional lung alveolar epithelial cells in 3D dynamic culture - Alsobaie, Sarah; Alsobaie, Tamador; Alshammary, Amal; Mantalaris, Sakis (Frontiers in Bioengineering and Biotechnology, 2023)
Understanding lung epithelium cell development from human induced pluripotent stem cells (IPSCs) in vitro can lead to an individualized model for lung engineering, therapy, and drug testing. In this study, we have produced mature type I pneumocytes in only 20 days without using feeder cells. We developed a protocol for lung epithelial differentiation using encapsulation of human IPSCs in 1.1% (w/v) alginate solution within a rotating wall bioreactor system. The aim was to reduce exposure to animal products and laborious interventions in the future. The three-dimensional (3D) bioprocess allowed cell derivation into endoderm, and subsequently into type II alveolar epithelial cells within a very short period. Cells successfully expressed surfactant proteins C and B associated with type II alveolar epithelial cells, and the key structure of lamellar bodies and microvilli was shown by transmission electron microscopy. Degeneration signs of apoptosis were observed, which differs from cells developed in static cultures. The survival rate was the highest under dynamic conditions, which reveal the possibility of adapting this integration for large-scale cell production of alveolar epithelial cells from human IPSCs. The aim of the present study was to develop a strategy for the culture and differentiation of human IPSCs into alveolar type II cells using an in vitro system that mimics the in vivo environment. We hypothesized that hydrogel beads would offer a suitable matrix for 3D cultures and that the high-aspect-ratio vessel bioreactor can be used to mimic dynamic microgravity conditions. This is expected to increase the differentiation of human IPSCs relative to the results obtained with traditional monolayer cultures.